2004
DOI: 10.1007/s00267-003-0168-1
|View full text |Cite
|
Sign up to set email alerts
|

Using Sediment Budgets to Investigate the Pathogen Flux Through Catchments

Abstract: We demonstrate a materials budget approach to identify the main source areas and fluxes of pathogens through a landscape by using the flux of fine sediments as a proxyfor pathogens. Sediment budgets were created for three subcatchment tributaries of the Googong Reservoir in south-eastern New South Wales, Australia. Major inputs, sources, stores, and transport zones were estimated using sediment sampling, dam trap efficiency measures, and radionuclide tracing. Particle size analyses were used to quantify the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The multi‐resolution valley bottom flatness index (MrVBF) identifies flat valley bottoms and WI indicates the degree of wetness (Wang & Laffan, 2009). These indices indicate potential zones of transport for many materials, particularly sediment and other materials in excess water flow (Whiteway et al , 2004). Therefore, MrVBF and WI act indirectly in the identification of some of the great groups, particularly Haplosalids, Haplocalcids and Calcigypsids.…”
Section: Resultsmentioning
confidence: 99%
“…The multi‐resolution valley bottom flatness index (MrVBF) identifies flat valley bottoms and WI indicates the degree of wetness (Wang & Laffan, 2009). These indices indicate potential zones of transport for many materials, particularly sediment and other materials in excess water flow (Whiteway et al , 2004). Therefore, MrVBF and WI act indirectly in the identification of some of the great groups, particularly Haplosalids, Haplocalcids and Calcigypsids.…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed that the terrain attributes were the most effective characteristics in predicting the family classes, indicating that the relief is the most important factor explaining the formed soils. The wetness index MrVBF indicates potential zones of transport for many materials, particularly sediment and other materials in excess water flow (Whiteway et al, 2004). The geomorphology map also was a powerful predictor in model fitting.…”
Section: Multi-nomial Logistic Regression (Lr)mentioning
confidence: 99%
“…Previous research includes the work by Loughran et al (1981Loughran et al ( , 1986Loughran et al ( , 1992) in a small (1.7 km 2 ) subcatchment of the Hunter River (coastal New South Wales). More recently, Whiteway et al (2004) developed fine sediment budgets for three small upland catchments (0.38-1.52 km 2 ) in southern New South Wales, which was used to investigate pathogen flux through the catchments. The aims of this study are twofold: firstly, to undertake detailed short-term monitoring of erosion processes, sediment sources, channel storage, and catchment fine sediment output; and secondly, to integrate this data into a sediment budget for the study catchment in order to provide insight into slope-channel coupling and in-channel sediment storage dynamics.…”
Section: Introductionmentioning
confidence: 99%